EDUKASI MENGENAI BAHAYA NARKOBA DIKALANGAN REMAJA - Lyanna Arsianti (Jurnal Pengabdian Masyarakat Kesosi, 2020)
Drug abuse can damage the mental development of the younger generation both for the user and for others. Drugs as substances that are indispensable for treatment in health services are often misused not in accordance with treatment standards and if accompanied by illicit drug trafficking will have very detrimental effects on individuals or society, especially the younger generation and can even pose a very big danger to life and values. the nation's cultural values ​​which in the end will weaken national resilience. From a legal perspective, drugs are very dangerous for the younger generation. Children and adolescents need guidance and knowledge about the dangers of drugs so they don't use and fall into this world. This community service aims to increase knowledge about drugs and the dangers of drugs if consumed. The method used is counseling and lectures by making presentations using Power Point as well as conducting discussions, and asking questions with the extension participants. This community service implementation activity can run well and sustainably.